A novel and resumable Schiff-base fluorescent chemosensor for Zn(II). Issue 26 (29th June 2016) - Yan, Jun; Fan, Long; Qin, Jing-can; Li, Chao-rui; Yang, Zheng-yin
Graphical abstract: Proposed binding mode for interaction of Zn 2+ withL . Highlights: An easy-to-make Schiff-base fluorescent sensor was designed and synthesized. The probe exhibited high selectivity and sensitivity for Zn 2+ over other metal ions. The chemosensor showed excellent restorability. CN isomerization and PET can be used to explain the high selectivity of the probe. Abstract: A new resumable Schiff-base fluorescent probe 7-methoxychromone-3-carbaldehyde-(3′-hydroxy-2′-naphthaleneformyl) hydrazone (L ) was designed and synthesized for selective recognition Zn 2+ . With the titration and the ESI-MS spectra data, we reached the conclusion that the binding ratio betweenL and Zn 2+ was determined to be 1. The sensor showed a strong fluorescence enhancement in ethanol system of Zn 2+ (excitation 430 nm and emission 498 nm). And the enhancement may be due to CN isomerization and Photoinduced Electron Transfer (PET).